Absorption curves - mineral-extraction under an aeroponic system for white chrysanthemum (Dendranthema grandiflorum (Ramat.) Kitam. cv. Atlantis White) (2018)
The aim of this study focused on the construction of the absorption and extraction curves under an aeroponic system for D. grandiflorum cv. Atlantis White, and therefore, propose the periods of maximum and minimum nutrient accumulation from aboveground, root and total biomass. Vegetative cycle of the plant, measured from the day after transplantation (dat) to aeroponic system, and the first day of court lasted 49 days. Evaluations were carried out each week on plants, in absolute competition. For the average aboveground biomass, three replicates were recorded. To obtain total root biomass only one sample, was measured. Therefore, total biomass in average, had achieved 130.9313 g.plant-1, where 72.26% (94.163 g) corresponded to the aboveground biomass and 27.74% (36.3183 g) to root biomass. From nutrient contents reported in tissue analysis and biomass, nutrients absorbed-extracted were calculated. Overall, two plant stages development in nutrient absorption were observed as follows: the first, at day 21 dat; and second, from day 22 to day 49 dat. In this study, the reported elements (N, P, K, Ca, Mg and S), its accumulation during the first stage did not exceeded 29%, except for S, which reached 30.19%. Consequently, the mostly close to 70% nutrients were absorbed in the second stage of development, which coincided with the plant reproductive stage.